If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (2 * 3x + 5) = 945 Multiply 2 * 3 2x + (6x + 5) = 945 Reorder the terms: 2x + (5 + 6x) = 945 Remove parenthesis around (5 + 6x) 2x + 5 + 6x = 945 Reorder the terms: 5 + 2x + 6x = 945 Combine like terms: 2x + 6x = 8x 5 + 8x = 945 Solving 5 + 8x = 945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 8x = 945 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = 945 + -5 8x = 945 + -5 Combine like terms: 945 + -5 = 940 8x = 940 Divide each side by '8'. x = 117.5 Simplifying x = 117.5
| 7(2n+4)=9(4n+5)+7 | | 4d^2-2d=0 | | 4/5x=32 | | -3x+4=4x-17 | | 6(x-2)/9=4(x+1)/12 | | 7(x+1)+7=2x+5(3+x) | | -9+12x+13k-5x-2k-25= | | 5x-3=-3x+1 | | -19=5t | | -9(x-10)=17-8x | | 3x+(2*3x+5)=945 | | 6x-(7x+6)=4x-26 | | y=3.2x+0.7 | | 1.50x+2.00=20 | | 14=-7u | | 6y+2(y-9)=6(y+1)-3 | | x-5x-60-x-13=-17 | | 7(2n+5)=8(6n+1)+6 | | k(2k+2)-6(2k+4)=k(2k-4)+(6k+9) | | -30/6= | | x+12=2x+3+9(x-3) | | 3(x-4)-8=-5(-5x+2)-8x | | 15x+21=4(3x+6)+3x-3 | | 9+36/3^2 | | 5(x-3)=2(x+9) | | 3x-5=12x-18 | | 5(y+8)+y=3(y+4)-8 | | 8x+2=8(x-1) | | 2x-7(x+9)=11 | | 9(w+6)=-8w+3 | | (3x-1)(x+2)=20 | | 3(x-1)+5x-6= |